Recurrent SARS-CoV-2 Infection and Impaired Immunologic Response in a Pediatric Oncologic Patient While Treated With Radiochemotherapy. Issue 6 (6th May 2022) - Eichholz, Thomas; Arendt, Anne-Marie; Holzer, Ursula; Seitz, Christian; Rabsteyn, Armin; Ganzenmueller, Tina; Klein, Reinhild; Walz, Juliane; Lang, Peter
Abstract : Immune responses to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in pediatric patients with malignant disease may be affected by tumor therapy. Here, we report the case of a child with rhabdomyosarcoma and recurrent SARS-CoV-2 infection. Immunologic responses, analyzed by T-cell activity and anti-viral IgG levels, were impaired and not durable as a result of intensive radiochemotherapy.